Analysis of SMS text messages in Filipino - Cabatbat, Josephine Jill
We report a study on the features of SMS text messages in Filipino. Focusing on the changes in the constituent unigrams and bigrams, we analyze the changes in the Filipino language form due to different styles of texting. Drawing on the bigram frequency distributions and texters style preferences, a method that can be used in approximate matching of SMS messages is introduced. Moreover, by analyzing the information change in a contemporary text after SMS translation, texting was explained as a coding process prompted by Least Effort Principle, a deterministic theory known to be guiding many aspects of human behavior. Lastly, presented is the application of unigram language network as an alternative system for analysis of SMS language.